A retrospective cohort study of H-type hypertension and its influence on the prognostic effect in patients with non-dialysis CKD - Cai, Xiaoyu; Ju, Menglei; Jiang, Xinying; Ge, Shengnan; Han, Yuzhang; Lin, Shumin; Peng, Hui; Li, Man; Wang, Cheng (Frontiers in Nutrition, 2025)
BackgroundThe study aimed to investigate the impact of coexistence of hyperhomocysteinemia (HHcy) and hypertension (HTN), referred to as H-type hypertension on kidney outcomes and major adverse cardiovascular and cerebrovascular events (MACCEs) in patients with non-dialysis chronic kidney disease (CKD).MethodsThis retrospective study enrolled 2,558 non-dialysis CKD patients admitted to two medical centers in China between 2010 and 2022. The participants were divided into four groups according to baseline blood pressure and homocysteine levels: (1) normotension with normohomocysteinemia; (2) normotension with HHcy; (3) hypertension with normohomocysteinemia; and (4) H-type hypertension. Cox regression model was applied to assess the relationship between these groups and renal outcomes/MACCEs. Mediation analysis was performed to assess the influence of HHcy on the link between hypertension and the outcomes.ResultsThree hundred and eighty renal endpoint events and 211 MACCEs were recorded. The H-type hypertension group demonstrated higher incidence of renal events (age-adjusted incidence: 83.71/1,000 person-years vs. 24.50/1,000 person-years) and MACCEs (age-adjusted incidence: 41.28/1,000 person-years vs. 17.21/1,000 person-years) compared to the normotension with normohomocysteinemia group. After adjusting for confounders, H-type hypertension independently elevated the risk of kidney outcomes by 312% (HR = 4.12, 95% CI: 2.66–6.37) and MACCEs by 127% (HR = 2.27, 95% CI: 1.28–4.02). No statistically significant mediated effect of HHcy on the relationship between hypertension and renal outcomes or MACCEs was observed.ConclusionH-type hypertension is associated with renal deterioration and cardiovascular events in non-dialysis CKD patients, early detections of H-type hypertension are essential to enhancing the prognosis for CKD patients.